Peer review of the pesticide risk assessment of the active substance paraffin oil (CAS 8042‐47‐5, chain lengths C17–C31) - European Food Safety Authority (EFSA); Fernando Álvarez; Maria Arena; Domenica Auteri; Sofia Batista Leite; Marco Binaglia; Anna Federica Castoldi; Arianna Chiusolo; Angelo Colagiorgi; Mathilde Colas; Federica Crivellente; Chloe De Lentdecker; et al. (EFSA Journal)
Abstract The conclusions of the European Food Safety Authority (EFSA) following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State, Greece, and co‐rapporteur Member State, France, for the pesticide active substance paraffin oil are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012, as amended by Commission Implementing Regulation (EU) No 2018/1659. The conclusions were reached on the basis of the evaluation of the representative uses of paraffin oil as an acaricide and insecticide on potatoes, ornamentals (flower bulbs) and orchards (pear/apple), on pome fruit and stone fruit, on field and permanent protected fruiting vegetables and on field and permanent protected roses and on citrus. The reliable end points appropriate for use in regulatory risk assessment are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are reported where identified.